Popliteal artery thrombosis a TKA complication due to retractor: a report of two cases treated with endovascular reconstruction - Zhou, Meng; Shen, Huiliang; Cao, Guanglei; An, Shuai (Annals of Joint; Vol 2 (October 2017): Annals of Joint, 2017)
Arterial thrombosis after total knee arthroplasty (TKA) is a rare but limb-threatening complication, and early diagnosis and intervention are critical. However, delayed diagnosis is not uncommon, even in high-volume joint replacement centers. Some studies have indicated that patients with preexisting vascular disease have an increased risk of vascular injury during TKA. Thus, we report two cases from our center, which were treated during a 4-month period, that developed acute popliteal artery thrombosis immediately after TKA, despite the absence of preoperative vascular abnormalities in the affected lower limbs. In both cases, absence of a foot pulse was detected in time to successfully manage the complication using endovascular stent deployment, rather than open surgery. After the second case, the complications were attributed to improper use of single-pronged retractors, which were applied to the posterior surface of the tibial plateau. No other cases with similar complications have occurred. Thus, these cases indicate that direct instrument-related blunt injury can cause popliteal arterial thrombosis after TKA, and that the thrombosis can be successfully treated using the endovascular approach.